The CROWN Act of 2019 and the Possible Implementation of it in Title VII of the Civil Rights Act of 1964 - Berry, Barbara (My University, 2024)
The original Title VII of the Civil Rights Act of 1964 was meant to resolve many issues in the U.S. as it pertained to racial discrimination. The present study seeks to determine ways Title VII of the Civil Rights Act of 1964 may be expanded. One proposal is to expand the protection of African Americans from being discriminated against based on their innate hair texture or desired hairstyle. Dove, as a part of Unilever, developed a petition to initiate the discussion of race-based discrimination, which targets individuals whose desired hairstyle is its natural state or a cultural staple.
Keywords: Political Science; Public administration; Public policy (Law); Dissertations, Academic--United States; Equality; Hair--Analysis; Segregation; Civil Rights Act of 1964 (United States); Hair